The competential process: A new procedural remedy to void sentences or leave them without effects? (A chronicle regarding judgment No. 006-2006-PC / TC issued by the Constitutional Court - Palomino Manchego, José F. (2007)
Gathered for the first time in the Political Constitution of 1993, the Process of Competition is a suitable way to dissolve the existingconflicts, as far as the competitions granted by the Political Constitution to the diverse organs of constitutional relevance and to the other organs of the State. For that reason, starting off of an analysis of the normativity applicable to it, the author takes care of the competential process by the study of sentences of the Constitutional Court related to the Judicial Power, in which he tries to distinguish the supposed existing tensions between this Court and the Judicial Power.